Analysis Of Employee Work Productivity at PT Putra Saluyu Sumedang - Amanah, Ameliana Putri Agustin Nur; Puspasari, Rd. Dewi; Amanda, Helles (SINTESA, 2025)
PT Putra Saluyu is a company engaged in construction services, namely formwork. In every company, of course, good Human Resource Management is needed, including PT Putra Saluyu, one of the important parts of Human Resource Management is Work Productivity. Therefore, this research aims to find out how employee work productivity and the obstacles faced and efforts made to increase employee work productivity. The method used in this research is a qualitative method with employee work productivity as the research theme. The research data was collected through interviews. The informants of this research are employees of PT Putra Saluyu. The research data was analyzed qualitatively using data collection, data reduction, data display and conclusion drawing. The results showed that employee work productivity was good. Then the efforts to improve employee work productivity are providing training, giving awards to outstanding employees, maintaining applicable regulations and coordination between employees and with external parties of the company.